Concept Of Consumer Protection Regarding The Availability Of Information On Snack Products Children In State Primary Schools - Tengku Emilia Angraini; Melky Suhery Simamora; Junaidi Lubis; Anisah bt Ahmad; Muhammad Salim Fauzi; Wahyu Hadi Wijaya (Outline Publisher, 2024)
The research focuses on consumer protection related to the availability of product information on children's snacks sold at public elementary schools (Public Alementary School) in Indonesia. Many snacks lack essential details such as nutritional information, waste management education, halal certification, ingredients, and Food and Drug Monitoring Agency license numbers on their packaging, which violates Indonesian regulations. This study aims to explore the concept of consumer protection regarding product information, children's rights to safe goods and services, and the implementation of consumer protection in public elementary schools. Using a qualitative research method with a normative-empirical juridical approach, the study collects primary data through interviews and secondary data from literature, journals, and other related sources. The findings indicate that consumer protection involves safeguarding consumer rights by ensuring adequate product information. Educating children as consumers is crucial for developing awareness of their rights. Public elementary schools play a vital role in ensuring that snacks sold are safe, of good quality, and meet hygiene standards. Schools should implement effective monitoring systems, including regular inspections of snack production and compliance with health standards. Additionally, consumer education at schools should teach children to choose healthy snacks, read food labels, and understand their rights as consumers, fostering informed decision-making and healthier choices.